"Did I push myself over the edge?": Complications of agency in psychosis onset and development. Issue 4 (1st October 2016) - Jones, Nev; Shattell, Mona; Kelly, Timothy; Brown, Robyn; Robinson, LaVome; Renfro, Richard; Harris, Barbara; Luhrmann, Tanya Marie
Abstract : Objective: To investigate the subjective experience of agency in the onset and early development of psychosis. Method: We conducted 19 in-depth interviews with a sample of individuals with self-reported diagnoses of schizophrenia and/or affective psychosis. Interviews focused on participants' experiences of agency and control in the onset and development of positive psychotic symptoms. Interviews were coded and transcripts analyzed by service-user researchers. Results: The majority of participants reported multiple ways in which they experienced their own agency or intentionality as involved in the initial onset of psychosis, in self-conscious engagement with symptom structure and content, and in their elaboration and development. For many, the moral implications of these felt experiences were considerable, at times leading to shame or guilt. Conclusion: Clinical accounts often stress the imposed, involuntary experience of symptoms and onset. Our project suggests that at least a subset of subjects with psychosis instead experience themselves as partly or fully "responsible" for onset, and actively involved in the shaping and elaboration of positive symptoms. In both clinical practice and future research, we argue that such complications should be explored and grappled with rather than downplayed.